1977
DOI: 10.1007/bf02082012
|View full text |Cite
|
Sign up to set email alerts
|

Final results of Coffey's ureterosigmoidostomy in noncarcinomatous diseases

Abstract: The present report on 67 patients, in whom a ureterosigmoidostomy was performed on the ground of a benign indication, is to take a critical attitude towards ureterosigmoidostomy. In about 60 per cent of the cases satisfactory or good results can be achieved. Final comparisons with other methods of derivation cannot be made, since a sufficiently great number of late results is not yet available. In our opinion, it is doubtful if there will ever be an alternative. The operator's judgment and experience will alwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…How ever, the frequencies of stomal stenosis and severe skin problems were low compared to that seen after the con struction of a cutaneous ureterostomy [7,8]. Likewise the frequencies of ascending urinary tract infections and hy perchloremic acidosis were low compared to those seen after the construction of Coffey's ureterosigmoidostomy [9], Like Pitts et al [4] we found deterioration of renal function in about 10-20% of the patients (table VII). In approximately half of the cases this was due to dilatation of the upper urinary tract.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…How ever, the frequencies of stomal stenosis and severe skin problems were low compared to that seen after the con struction of a cutaneous ureterostomy [7,8]. Likewise the frequencies of ascending urinary tract infections and hy perchloremic acidosis were low compared to those seen after the construction of Coffey's ureterosigmoidostomy [9], Like Pitts et al [4] we found deterioration of renal function in about 10-20% of the patients (table VII). In approximately half of the cases this was due to dilatation of the upper urinary tract.…”
Section: Discussionsupporting
confidence: 50%
“…Most of these postoperative complications will be ob served with different frequencies after various types of urinary diversion [5,7,9]. Local complications from the bladder site or residual bladder and urethra will appear with the same frequency in all types of operations.…”
Section: Discussionmentioning
confidence: 99%